Psychosocial and contextual correlates of opioid overdose risk among drug users in St. Petersburg, Russia - Ilyuk Ruslan; Krupitsky Evgeny; Blinnikova Ksenia; Torban Mikhail; Green Traci C; Grau Lauretta E; Kozlov Andrei P; Heimer Robert (BMC, 2009)
Abstract Background Opioid overdose in Russia is a problem that has grown more severe as heroin abuse expanded over the past decade, yet few studies have explored it in detail. In order to gain a clearer understanding of the situation, 60 drug users, both in and out of drug treatment in St. Petersburg, were interviewed concerning their overdose experience and knowledge about overdose recognition and prevention. Methods Using a semi-structured interview, we sought to identify and describe local attitudes, knowledge and experience (both self-sustained and witnessed) of opioid overdose. Bi-variate and multiple logistic regressions were performed in order to identify the relationship between overdose experience and sociodemographic factors, risk behaviors, and clinical psychiatric measures. Results We found that having experienced or witnessed an opioid overdose within the previous year was common, overdose knowledge was generally high, but nearly half the participants reported low self-efficacy for effectively intervening in an overdose situation. In bivariate analyses, self-reported family problems (i.e., perceived problematic family interactions) were positively associated with both experiencing (t56 = 2.49; p < 0.05) and with witnessing a greater number of overdoses in the previous year (rhos = 0.31; p < 0.05). Having previously overdosed [Adjusted Risk Ratio (ARR) 1.7, 95% Confidence Interval (CI) 1.1-2.6] and higher SCL-90-R somatization scores (ARR 1.2, 95% CI 0.96 - 1.5) were independently associated in multivariable analyses with self-sustained overdose experience in the past year. Greater perceived likelihood of experiencing a future overdose and concern about medical problems were independently associated with witnessing a higher number of overdoses within the previous year. Over two thirds of the participants expressed interest in receiving training in overdose prevention and response. Conclusion Opioid overdose experience is very common among drug users in St. Petersburg, Russia, and interest in receiving training for overdose recognition and prevention was high. Future research should target the development of effective overdose recognition and prevention interventions, especially ones that include naloxone distribution and involve drug users' families.